Water Scarcity in the Mediterranean Perspectives Under Global Change - Sabater, Sergi; Barceló, Damià; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Water scarcity affects hydrologic resources, systems connectivity, biodiversity, water quality, and river ecosystem functioning. It has direct impacts on economic sectors that use and depend on water, such as agriculture, tourism, industry, energy and transport. The Mediterranean Basin is one of the regions in the world most vulnerable to climate changes, as well as one of the most impacted by human water demand. This volume provides an in-depth view of the water quality and quantity implications of water scarcity. It highlights its possible causes and describes the effects in regions under Mediterranean climate. The topics covered include climate effects, water resources (use, storage and new sources), water quality (chemical and microbiological), and the effects on ecosystems suffering from water scarcity. This book is addressed to scientists and students, but also to managers involved in the necessary decision making process to face future periods of drought.
Possible Climate Change Scenarios with Specific Reference to Mediterranean Regions -- Effects of Hydrologic Alterations on the Ecological Quality of River Ecosystems -- Metal Ecotoxicology in Fluvial Biofilms: Potential Influence of Water Scarcity -- Consequences of Climate Variability and Human Water Demand on Freshwater Ecosystems: A Mediterranean Perspective from the United States -- Water Quality in Reservoirs Under a Changing Climate -- Technologies for Water Regeneration and Integrated Management of Water Resources -- Reuse of Regenerated Waters Under Water Scarcity -- Decision Support Systems for Integrated Water Resources Management Under Water Scarcity -- Water-Borne Infectious Disease Outbreaks Associated with Water Scarcity and Rainfall Events -- Implications of Water Quality on Irrigation Practices Under Water Scarcity -- Effects of Wastewater Treatment Plants on Stream Nutrient Dynamics Under Water Scarcity Conditions -- Occurrence and Fate of Pharmaceuticals and Illicit Drugs Under Water Scarcity.
Keywords: Environmental management; Water pollution; Hydrogeology; Environmental chemistry; Water quality; Geochemistry; Environmental Management; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Hydrogeology; Environmental Chemistry; Water Quality/Water Pollution; Geochemistry